Valproate Treatment in an ALS Patient Carrying a c.194G>A Spastin Mutation and SMN2 Homozygous Deletion - Lucio Tremolizzo; Gessica Sala; Elisa Conti; Virginia Rodriguez-Menendez; Antonella Fogli; Angela Michelucci; Paolo Simi; Silvana Penco; Christian Lunetta; Massimo Corbo; Carlo Ferrarese (Case Reports in Neurological Medicine)
Here we report the case of an ALS patient found to carry both a novel heterozygous change (c.194G>A) within the spastin gene and a homozygous deletion of the SMN2 gene. The patient was started on valproic acid (VPA, 600 mg/die per os) considering the capacity of this drug of increasing survival motor neuron through an epigenetic mechanism. Patient clinical course and molecular effects of VPA on skin fibroblasts obtained from the proband are described. This c.194G>A spastin mutation might expand the previously known borders of type 4 spastic paraplegia (SPG4) and we suggest the intriguing possibility that the absence of SMN2 might have acted as a contributory risk factor for starting lower motor neuron damage. Exploring the relationship genocopy-phenocopy in selected ALS patients might represent an interesting strategy for understanding its clinical variability.